Evaluating Hypertension Risk Factors: A Study in Sidoarjo Regency, Indonesia - Sari, Vivin Fatma; Sunarti; Ranee, Sarinah (The Indonesian Institute of Science and Technology Research, 2024)
Hypertension is a public problem that is national-focused. The prevalence in Indonesia reaches 34.1%. Sodium intake, physical activity, central obesity status, and family history are risk factors for hypertension. This study aims to prove sodium intake, physical activity, central obesity status, and family history of hypertension. This cross-sectional approach, a quantitative method, was conducted in Sawotratap Village. Sixty-eight people underwent health checks at Posbindu Saworatap from February to November 2022 and only 63 met the criteria. Measurements of hypertension status using a digital sphygmomanometer, measuring sodium intake using the SQ-FFQ forms, measuring physical activity using a questionnaire, and measuring central obesity status with an abdominal circumference indicator measured by a meter with an accuracy of 1 mm. Data analysis using chi-square test. The results showed that there was a relationship between sodium intake and the incidence of hypertension. There is a relationship between central obesity status and the incidence of hypertension. There is a relationship between family history and the incidence of hypertension. There is no relationship between physical activity and the incidence of hypertension. Sodium intake, central obesity status, and family history are risk factors for hypertension. While physical activity was not associated with the incidence of hypertension.